Differential expression and processing of matrix metalloproteinase 19 marks progression of gastrointestinal diseases - Cervinková, M; Horák, P; Kanchev, I; Matěj, R; Fanta, J; Sequens, R; Kašpárek, P; Sarnová, L; Turečková, J; Sedláček, R (Folia biologica, 2014)
Matrix metalloproteinases (MMPs), responsible for extracellular matrix remodelling and processing of numerous soluble and cell-surface proteins, appear to play important roles in pathogenesis of gastrointestinal diseases. MMPs influence migration of inflammatory cells, mucosal destruction, matrix deposition and degradation. In this study, we analysed the expression of MMP-19 in the main forms of gastrointestinal diseases including inflammatory bowel diseases (IBD) such as ulcerative colitis and Crohn's disease, and colorectal carcinoma. We identified prominent MMP-19 expression in unaffected areas of intestinal epithelia and macrophages but not in other cells or tissues. Abundant expression of MMP-19 was also found in the endothelium of blood and lymphatic vessels of inflamed intestinal tissue. High MMP-19 immunoreactivity was also associated with macrophages in inflamed areas and myenteric plexuses. In comparison to the intestinal epithelium, all these cell types and compartments appeared to express MMP-19 irrespective of the disease pathogenesis and progression. Intestinal epithelia exhibited striking differential immunoreactivity for MMP-19. While immunoreactivity of monoclonal antibody recognizing the propeptide domain declined in virtually all IBD and colorectal carcinoma samples, other polyclonal antibodies against the hinge region and propetide domain did not show such an obvious decrease. Additional Western blotting analysis revealed that the antibodies against MMP-19 recognize differently processed forms of this MMP. The disappearance of immunoreactivity of the monoclonal anti-propeptide domain antibody does not mean down-regulation of MMP-19, but processing of the immature form. As this processing likely leads to the activation of this MMP, the differential staining pattern may be an important sign of disease progression.
Keywords: senioři; Reproducibility of Results; Disease Progression; gastrointestinální nemoci; Antibodies; protilátky; reprodukovatelnost výsledků; Gastrointestinal Diseases; Intestine, Small; progrese nemoci; Matrix Metalloproteinases, Secreted; Middle Aged; mužské pohlaví; metaloproteinasy secernované do matrix; HCT116 buňky; tenké střevo; posttranslační úpravy proteinů; Adult; mladý dospělý; Intestinal Mucosa; HCT116 Cells; Colon; Young Adult; ženské pohlaví; Protein Processing, Post-Translational; Humans; kolon; lidé středního věku; střevní sliznice; dospělí; Female; Aged; lidé; Male